Space-time bifurcation lines for extraction of 2D Lagrangian coherent structures - Machado, Gustavo Mello; Boblest, Sebastian; Ertl, Thomas; Sadlo, Filip (Computer graphics forum, 2016)
We present a novel and efficient technique to extract Lagrangian coherent structures in two-dimensional time-dependent vector fields. We show that this can be achieved by employing bifurcation line extraction in the space-time representation of the vector field, and generating space-time bifurcation manifolds therefrom. To show the utility and applicability of our approach, we provide an evaluation of existing extraction techniques for Lagrangian coherent structures, and compare them to our approach.
Gesehen am 22.05.2020